Epidemiological analysis of emerging and re-emerging arbovirus infections in Brazil between the years 2019 and 2020 (Research, Society and Development, 2021)
The objective was to analyze the incidence and prevalence of arbovirus infections (dengue, chikungunya and zika) transmitted by Aedes aegypti between the years 2019 to 2020, as well as the factors that promote their propagation. Thus, a bibliographic review of a qualitative nature and of a descriptive and exploratory character was carried out. The guiding question was: What is the epidemiological situation of arbovirus infections in Brazil between the years 2019 and 2020? The search was conducted in the databases: PubMed and SciELO, as well as, epidemiological data belonging to the Ministry of Health/Brazil website was used. The inclusion criteria were: complete national and international articles, available free of charge, published between January 2008 and January 2021 in English and Portuguese. As far as public health is concerned, arboviruses have generated great concern in the world. In 2020, 971.136 probable cases of dengue were reported up to Epidemiological Week (EW) 46, with an incidence rate of 462,1 cases/100.000 inhabitants, for Chikungunya, between EW 1 and 46, 78.808 probable cases were reported, with an incidence rate of 37,5 cases/100.000 inhabitants. In addition, for Zika, between EW 1 and 43, there were 7.006 probable cases reported in Brazil, with an incidence rate of 3,3 cases/100.000 inhabitants. Therefore, it is clear that arbovirus infections cause a huge impact on public health that goes from the identification of the causative agent to the vector control measures. With this, the importance of sanitation as a method to control the incidence and prevalence of arbovirus infections is emphasized.